Forest Products Annual Market Review 2022-2023 - United Nations Economic Commission for Europe (United Nations, 2024)
The Forest Products Annual Market Review 2022-2023 provides a comprehensive analysis of markets in the UNECE region and reports on the main market influences beyond the region. It covers products from the forest to the end user and from roundwood and primary processed products to value-added, housing and wood energy. Statistics-based chapters analyse the markets, sawn hardwood and wood-based panels. Underlying the analysis is a comprehensive collection of data. The Review highlights the role of sustainable forest products in international markets, discusses policies concerning forests and forest products, assesses the main trends and drivers, and analyses the effects of the current economic situation on forest product markets.